Selection on Ability and the Early Career Growth in the Gender Wage Gap - Eduardo Fraga; Gustavo Gonzaga; Rodrigo R. Soares (Institute of Labor Economics (IZA), 2017)
This paper analyzes the effect of selection on ability on the evolution of the gender wage gap during the first years of professional life. We use longitudinal data with 16 years of the early career history of formal sector workers in Brazil. The panel allows us to build a measure of unobserved ability that we use to analyze the dynamics of labor market selection across genders as individuals age. We focus on the cohort born in 1974, for which we have a close to complete history of formal labor market participation. For this cohort, the average ability of formally employed men improved in relation to that of women during the first years of professional life. The selection of men and women into the labor market was similar at age 21, but by age 31 high-ability men (one standard deviation above the mean) had a probability of employment 1.6 percentage point higher than their high-ability female counterparts. This contributed to the increase in the conditional gender wage gap observed in the early career, as the ability distribution of employed women deteriorated in relation to that of employed men. Our estimates suggest that, for the 1974 cohort, this mechanism explains 32% of the cumulative growth in the conditional gender wage gap between ages 21 and 36.
Keywords: J16; J21; J31; J71; 330; ability; selection; gender wage gap; lifecycle